Road health: strategy to investigate metabolic syndrome in truck drivers (Research, Society and Development, 2020)
The objective of this investigation carried out by the Reference Center for Workers' Health - Paraíba (Centro de Referência Saúde do Trabalhador - Média Paraíba) was to analyze some aspects of the health of truck drivers who passed through the axis that corresponds to the road  between the cities of Rio de Janeiro and São Paulo, identifying possible changes related to the Syndrome Metabolic. Method: 526 truck drivers from the interior of Rio de Janeiro, on the Presidente Dutra BR-116 Highway, were evaluated. A questionnaire was used, which analyzed the changes in blood glucose, blood pressure, overweight, smoking, and alcoholism. Data was collected using a semi-structured script and analyzed using descriptive statistics techniques, all through tables. Results: 31.5% of workers were aged from 40 to 49 years, 45.4% had changes in blood glucose, 52.8% had changes in blood pressure with the limits considered by the Ministry of Health above the national average, 32,6% were overweighted, 38.5% were obese, 19.2 reported being smokers, and 50.1 reported consuming alcoholic beverages. Conclusion: Several associated aspects intensify the appearance of the metabolic syndrome, with risks of serious health problems compromising the quality of life of these workers. The aim of this article is to raise new research with these professionals.